Body changes: antiretroviral therapy and lipodystrophy syndrome in people living with HIV/aids Alteraciones corporales: terapia antirretroviral y síndrome de la lipodistrofia en personas que viven con VIH/SIDA Alterações corporais: terapia antirretroviral e síndrome da lipodistrofia em pessoas vivendo com HIV/AIDS - Luciana Castelar Tsuda; Mariana Machado da Silva; Alcyone Artioli Machado; Ana Paula Morais Fernandes (Revista Latino-Americana de Enfermagem, 2012)
OBJECTIVE: to identify the different types of morphological alterations from lipodystrophy syndrome (LS) in outpatients and relate them to the therapeutic regimen used. METHOD: a cross-sectional study which recruited 60 patients with HIV and LS and 79 without LS, who consented to interview and data collection from their medical notes. RESULTS: the region most affected by lipoatrophy was the face; by lipohypertrophy, the abdomen, and by the mixed form, the alterations to the abdomen, face, and upper and lower limbs. CONCLUSION: among the therapeutic regimens, that comprised of zidovudine, lamivudine and efavirenz seemed to protect against LS. Nursing can act in the early identification of the changes, as well as providing guidance and support for patients affected by the changes in their body image. OBJETIVO: identificar los diferentes tipos de alteraciones morfológicas del Síndrome de la lipodistrofia (SL) en pacientes de los servicios de ambulatorio y relacionarlas al esquema terapéutico utilizado. MÉTODO: estudio transversal en lo que fueron reclutados 60 pacientes con VIH y la SL y 79 sin la SL, que consintieron entrevista y recogida de datos en prontuario. RESULTADOS: la región más acometida por la lipoatrofia fue la cara; por la lipohipertrofia el Abdomen y por la forma mixta las alteraciones en Abdomen, cara, miembros superiores e inferiores. CONCLUSIÓN: entre los esquemas terapéuticos, el compuesto por la zidovudina, lamivudina y efavirenz pareció proteger contra la SL. La enfermería puede actuar en la identificación precoz de las alteraciones, además de suministrar orientaciones y apoyo a los pacientes acometidos por los cambios en la imagen corporal. OBJETIVO: identificar os diferentes tipos de alterações morfológicas da síndrome da lipodistrofia (SL) em pacientes dos atendimentos ambulatoriais e relacioná-las ao esquema terapêutico utilizado. MÉTODO: estudo transversal, para o qual foram recrutados 60 pacientes com HIV e SL e 79 sem a SL, que consentiram entrevista e coleta de dados em prontuário. RESULTADOS: a região mais acometida pela lipoatrofia foi a face; pela lipo-hipertrofia o abdome e pela forma mista as alterações em abdome, face, membros superiores e inferiores. CONCLUSÃO: dentre os esquemas terapêuticos, o composto pela zidovudina, lamivudina e efavirenz pareceu proteger contra a SL. A enfermagem pode atuar na identificação precoce das alterações, além de fornecer orientações e apoio aos pacientes acometidos pelas mudanças na imagem corporal.